HUKUM PERKAWINAN DI INDONESIA (Kajian Hukum Berkeadilan Gender dalam Kerangka Feminis Legal Theory) - Moch. Fakhri (MUWAZAH : jurnal kajian gender, 2015)
This study set out from the issue of marriage law in Indonesia were inactiveness of women. This happens because the legal culture of the legislators was built with a base value of patriarchy. The consequence is the demand for gender equality and equity. Gender equality can not be achieved within the institutional structures that currently applies ideological, because the condition of women are still regarded as inferior then the need for a democratic legal system that allows women to be able to define themselves. Thus the legal system can not be implemented in authoritarian (centralized) by a certain group or nation